Description of the female of P. pauferrense Rodrigues, Cizauskas & Rheims, 2018 and three new species of Paracymbiomma Rodrigues, Cizauskas & Rheims, 2018 (Araneae: Prodidomidae) from Brazil - Cizauskas, Igor; Brescovit, Antonio D.; Rodrigues, Bruno V. B.; Rheims, Cristina A. (Zootaxa, 2024)
In this paper, we describe three new species of Paracymbiomma Rodrigues, Cizauskas & Rheims, 2018 and the female of P. pauferrense Rodrigues, Cizauskas & Rheims, 2018. Two species are restricted to the iron caves of the Carajás Speleological Unit, in the state of Pará, Brazil: Paracymbiomma pepita sp. nov. (male, female), from Serra Leste, Curionópolis and P. otxurucu sp. nov. (male, female) from Serra Sul, Canaã dos Carajás and Parauapebas. Paracymbiomma una sp. nov. (male, female) is described from Reserva Biológica do Una, Una, Bahia, Brazil. In addition, we list additional material collected in caves and deposited in arachnological collections in Brazil, provide an identification key and updated distribution map for all known species of the genus.